Prediction of Left Ventricle Function from Pre-Operative Left Ventricle End-Systolic Dimension in Mitral Valve Replacement: Prediction of Left Ventricle Function from Pre-Operative Left Ventricle End-Systolic Dimension - Saleem, Wardah; Iqbal, Fayaz; Saleem, Fatima (Pakistan Journal of Health Sciences, 2022)
Rheumatic heart disease is an endemic in developing countries. The most common valve affected is the mitral valve for which mitral valve replacement is done. Left Ventricle Function (LVEF) is used to measure the prognosis of patients after MVR. Patients with a good LVEF perform better with less morbidity and mortality in comparison to patients with low post-operative EF. Therefore, prediction of post-operative EF is mandatory in patient’s selection and post-operative management. Objective: To determine the effect of pre-operative left ventricular end-systolic dimension in predicting postoperative LV function in mitral valve replacement. Methods: A total of 100 patients with mitral valve replacement were selected for the research. The study was conducted at the cardiac surgery department of National Institute of Cardiovascular Diseases, Karachi from April 2022 to October 2022. Results: The mean age of patients was 37 ± 10 years, LVESD: 34.7 ± 8.4mm, LVEDD: 51.1 ± 9.1mm, PASP: 44 ± 11mmHg, and EF of 55 ± 9%. Patients having Left ventricular end-systolic dimension (LVESD)> 38 mm had a significant post-operative left ventricular dysfunction after mitral valve replacement than patients having a pre-operative LVESD < 38mm (p= 0.003). Moreover, patients having a pre-operative LV dysfunction (EF <55%) were more prone to post-operative LV dysfunction(p=0.02). However, pre-operative LVESD is a more sensitive predictor of post-operative LV dysfunction than pre-operative LVEF (0.003<0.02). Conclusion: Left Ventricular End-Systolic Dimension (LVESD) is a more sensitive parameter as compared to pre-operative LV ejection fraction (LVEF) in predicting post-operative LV ejection fraction (LVEF) after mitral valve replacement (MVR).